2008
DOI: 10.1016/j.ahj.2007.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous “hybrid” percutaneous coronary intervention and minimally invasive surgical bypass grafting: Feasibility, safety, and clinical outcomes

Abstract: Surgical and percutaneous coronary artery intervention revascularization are traditionally considered isolated options. A simultaneous hybrid approach may allow an opportunity to match the best strategy for a particular anatomic lesion. Concerns regarding safety and feasibility of such an approach exist. We examined the safety, feasibility, and early outcomes of a simultaneous hybrid revascularization strategy (minimally invasive direct coronary bypass grafting of the left anterior descending [LAD] artery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 26 publications
5
79
0
6
Order By: Relevance
“…32,48 -50 In many studies, however, the length of stay depended on the timing of a second staged procedure rather than reflecting postoperative recovery per se. The most impressive reductions were reported by Kon et al 48 and Reicher et al, 49 from the same institution, who showed that compared with conventional OPCABG, simultaneous HCR with a MidCAB approach led to a 20-fold reduction in intubation times and cut hospital stay almost in half. Patients were discharged after a mean of only 3.7 days and were 7 times more likely to return to work within 1 month.…”
Section: Real-world Advantages: Quicker Recovery Patient Satisfactiomentioning
confidence: 60%
See 1 more Smart Citation
“…32,48 -50 In many studies, however, the length of stay depended on the timing of a second staged procedure rather than reflecting postoperative recovery per se. The most impressive reductions were reported by Kon et al 48 and Reicher et al, 49 from the same institution, who showed that compared with conventional OPCABG, simultaneous HCR with a MidCAB approach led to a 20-fold reduction in intubation times and cut hospital stay almost in half. Patients were discharged after a mean of only 3.7 days and were 7 times more likely to return to work within 1 month.…”
Section: Real-world Advantages: Quicker Recovery Patient Satisfactiomentioning
confidence: 60%
“…Some reports suggest that simultaneous HCR using a combination of MidCAB and DES incurs costs of $3000 to $4000 more per patient than conventional OPCABG. 33,49 In contrast, Kon et al 48 performed a detailed cost analysis and found that although intraprocedural costs were greater because of a combination of longer operative times and use of DES, this finding was offset by reduced postoperative expenditure from shorter intubation and hospital stay compared with OPCABG. Given that OPCABG represents the best available evidence-based surgical approach for cost savings 8,53 and that we have comparatively less experience with minimally invasive approaches to the technique, we can only anticipate that greater experience and technical skill will lead to superior longer-term financial saving.…”
Section: Real-world Advantages: Quicker Recovery Patient Satisfactiomentioning
confidence: 93%
“…Недостатками являются возможность острых коронарных со-бытий в бассейнах нереваскуляризированных ОА и ПКА при проведении первого этапа, а также воз-можность неуспешного последующего ЧКВ при сложных техниках стентирования, риск рестеноза и тромбоза стента. При неуспешном ЧКВ возни-кает вопрос о необходимости повторной прямой реваскуляризации через срединную стернотомию [23,[43][44][45][46][47].…”
Section: в и ганюков р с тарасов и дрunclassified
“…Nos casos em que a ICP é realizada primeiramente, a DAP é iniciada antes do procedimento hemodinâmico e mantida durante a realização da CRM. (134) Quando a RMH é realizada de maneira simultânea, a CRM é realizada apenas sob o uso de heparina e ao final da anastomose ATI -IVA ou imediatamente antes da ICP, é realizada uma dose de ataque de clopidogrel, através de uma sonda naso-gástrica, de 300 a 600 mg. (129,(136)(137)(138)(139) Uma outra alternativa seria uma dose inical de clopidogrel durante a indução anestésica, (135) já que o pico de inibição plaquetária do clopidogrel ocorre entre 4 e 24 horas após sua administração, permitindo que a RMH simultânea seja realizada com maior segurança. (140,141) Muito ainda precisa ser discutido em relação à melhor forma de realizar a DAP na RMH, precisaremos aguardar por melhores evidências na literatura, como grandes estudos prospectivos e randomizados.…”
Section: Terapia De Antiagregação Plaquetáriaunclassified
“…(129,130,142,149) Nos pacientes submetidos a RMH, excelentes taxas de patência do enxerto de ATI -DA têm sido relatadas. (150) têm sido publicadas variando de 93% a 100% no pós operatório imediato, (130,133,140,144,146,151,152) e de 90% (139) a 94% (137) …”
Section: Terapia De Antiagregação Plaquetáriaunclassified